Association between serum carotenoids and hyperuricemia: a cross-sectional study based on NHANES 2001–2006 - Chen, Pengfei; Miao, Lina; Zhang, Lixiao; Du, Jianpeng; Guo, Ming; Shi, Dazhuo (Frontiers in Nutrition, 2024)
Purpose: This study aims to investigate the association between serum carotenoids and hyperuricemia.Methods: Data were sourced from the National Health and Nutrition Examination Survey (NHANES) between 2001 and 2006. Hyperuricemia was defined as serum uric acid (UA) levels of ≥ 7 mg/dL for males and ≥ 6 mg/dL for females. Serum carotenoid levels were measured using high-performance liquid chromatography.Multivariate linear regression was used to analyze the correlation between serum carotenoids and UA levels. Multivariate logistic regression and restricted cubic spline (RCS) analyses were performed to explore the potential association between serum carotenoids and hyperuricemia. Additionally, subgroup and interaction analyses were conducted to determine variations across different population groups.Result: This cross-sectional study included 13,561 participants. Multivariate linear regression analysis revealed that higher levels of serum carotenoids were correlated with lower UA levels. Specifically, the beta coefficients (β) and 95% confidence intervals (CIs) were as follows: α-carotene (-0.23 [-0.31,-0.15]), β-carotene (-0.30 [-0.38,-0.21]), β-cryptoxanthin (-0.17 [-0.25,-0.09]), lutein/zeaxanthin (-0.12 [-0.20,-0.04]), and total serum carotenoids (-0.25 [-0.33,-0.16]). However, lycopene showed no significant correlation with UA (-0.01 [-0.09,0.08]). Multivariate logistic regression analysis indicates a significant inverse association between serum carotenoids and the risk of hyperuricemia. The odds ratios (ORs) and 95%CIs were as follows: α-carotene (0.61 [0.49, 0.77]), β-carotene (0.67 [0.51, 0.86]), β-cryptoxanthin (0.69 [0.51, 0.88]), lutein/zeaxanthin (0.72 [0.56, 0.97]), lycopene (0.82 [0.67, 1.00]) and total serum carotenoids (0.73 [0.57, 0.92]). RCS analysis indicated a potential nonlinear relationship between lycopene and hyperuricemia, with an inflection point at 33.45 µg/dL. Subgroup and interaction analyses demonstrated that the inverse association remained consistent across various demographic groups.Conclusions: This study found that higher serum carotenoid levels are associated with lower UA levels and reduced risk of hyperuricemia. Notably, while lycopene was associated with reduced hyperuricemia risk, its effect showed some heterogeneity.